A Study of Psi-Function (Journal of Informatics and Mathematical Sciences, 2020)
The aim of this paper is to introduce a new generalization of the well-known, interesting and useful Fox \(H\)-function and \(I\)-function into generalized function, namely, the Psi-function. From which authors obtained I-function defined by Saxena [17] and Rathie [8]. Convergent conditions, elementary properties, and special cases have also been given.
Keywords: \(I\)-function; \(H\)-function; Mellin transform; Laplace transform; General class of polynomials; Struve's function